Implementation of Islamic Education Learning with CTL (Contextual Teaching and Learning) approach for Autism Spectrum Disorder (ASD) Children at SLB Mitra Ananda - Sigit Raharja; Endang Sri Handayani (UIN Raden Mas Said Surakarta, 2026)
This research is motivated by the limitations of conventional, teacher-centered Islamic Education (PAI) models, which often fail to meet the complex needs of students with special needs, particularly those with Autism Spectrum Disorder. Such methods frequently result in ineffective information processing and low engagement. Consequently, this study analyzes the implementation of the Contextual Teaching and Learning (CTL) model at SLB Mitra Ananda, identifying both supporting and inhibiting factors. Employing a qualitative descriptive approach, data were gathered from PAI teachers and students through observation, interviews, and documentation. The findings demonstrate that the CTL model was effectively implemented by integrating its seven core components: constructivism, inquiry, questioning, learning community, modeling, reflection, and authentic assessment. This approach was applied to subjects including ethics (akhlak), prayer and wudu instruction, Quranic recitation, and Islamic art. Success was supported by strong teacher-parent collaboration, effective role-modeling, and conducive school facilities. However, challenges such as limited teacher preparedness and restricted instructional time were identified. Ultimately, this study highlights the necessity of reinforcing strategic, contextual learning frameworks to enhance the educational development and functional understanding of PAI for students on the autism spectrum.